Pengaruh daya tarik dan E-WOM terhadap keputusan berkunjung melalui minat berkunjung sebagai variabel intervening - Hari Purwanto; Dian Citaningtyas Ari Kadi; Galuh Rismawati (MBR (Management and Business Review), 2021)
The purpose of this study was to determine the effect of Attractiveness and E-WOM on Decisions made through Interest as an Intervening Variable. The study used a quantitative approach with a sample of 269 respondents. Questionnaires were used for data collection, and data analysis using Path Analysis. The results of this study are attractiveness and E-WOM have a significant effect on visiting interest. Attractiveness and E-WOM have a significant effect on decisions. Path test (Path Analysis) found that interest can mediate the effect of attractiveness on decisions and interest can mediate the effect of E-WOM on decisions.